Status of university librarian in the governance structure of Nigerian universities (2021)
This paper examines the status of University Librarians in the administrative structure of academic libraries, considering their tenure, the influence they wield in University management, and their academic status within the University system. A descriptive survey research design was adopted for the study. Thirty universities were surveyed. Questionnaire and interview were used as data collection tools to gather information from University librarians of Private, State and Federal universities in Nigeria. The qualitative data was analysed thematically after transcription, while quantitative data was analysed using percentages and mean. It was found that over the years, the status of University Librarians seems to diminish as their position is gradually eroded in the University system. The librarians are not treated fairly like other academics who are full time teachers. The service- oriented bias of professional librarians in academic libraries causes them to be relegated, more often than not, to the background in the university. Recommendations are made as to restructuring the university libraries to making the tenure and job specifications more inclusive of teaching, research and productivity oriented. University librarians should have more training in developing management skills and ideally, should be properly positioned within the governance structure of the university system.